Comprehensive characterization of pore structure in coal seams with abnormal gas emission in deep close range coal seam clusters - Anying YUAN; Xiaolu YANG; Junling HOU; Guangsheng FU (Meitan kexue jishu)
Coal and gas outburst accidents have always been a major problem in coal mine safety production. Pores and fissures in coal are the main places for gas adsorption and migration. It is of great significance to study the structural characteristics of pores and fissures for the prevention and control of gas disasters. Taking the abnormal gas emission coal seam of Xieqiao Coal Mine in Huainan Mining Area as the research object, Compares the areas without accidents and adjacent coal seams conducting experimental studies such as scanning electron microscopy (SEM) and low field nuclear magnetic resonance (NMR) to study the parameters of coal pore and fracture types, pore connectivity, pore size distribution, effective porosity, and permeability, and explores the influence of coal pore structure on gas adsorption and migration. The results show that the internal pore structure of coal body will affect its permeability, and the development of a large number of granular pores in coal body and the serious filling of minerals are not conducive to fluid migration. The T2 spectrum of saturated water coal samples in three regions shows three peaks in nuclear magnetic resonance time, mainly with short relaxation time. However, there are certain differences in the pore size distribution and connectivity of each coal body. The abnormal areas have abnormally developed micropores in the coal body, relatively undeveloped small and medium-sized pores, and poor connectivity between adsorption pores and transition pores, indicating that the differences in gas migration are related to pore size distribution and pore connectivity; The abnormal coal body in the area is conducive to gas adsorption but not conducive to gas diffusion, and the initial velocity of gas release is higher, making it more prone to gas abnormal outburst or outburst accidents when affected by mining; The proportion of micropores in coal is negatively correlated with effective porosity, while the proportion of small and medium-sized pores is positively correlated with effective porosity. The effective porosity is significantly linearly related to coal permeability, indicating that the pore size distribution of coal affects the effective porosity of coal, thereby affecting the permeability of coal; The effective porosity directly affects the permeability of coal seams and is also related to coal quality parameters, which can be used as one of the indicators to evaluate the properties of coal seams to a certain extent .